Evaluasi Modularity Index pada Sistem Plug-and-Play Renewable Power Station - Harjono, Dwi (Jurnal ELIT, 2026)
This study evaluates the modularity index in plug-and-play renewable power station systems designed to support the flexibility and scalability of renewable energy systems. The evaluation was carried out based on three main parameters, namely functional independence, interface standardization, and reconfiguration capability. Tests were carried out on three system configurations, namely the basic configuration, the expansion configuration with the addition of photovoltaic modules, and the battery module replacement configuration. The test results showed that the basic configuration had a modularity index value of 0.85. The addition of a photovoltaic module increases the modularity index value to 0.88, while the battery replacement configuration results in the highest modularity index value of 0.90. These results show that the proposed modular architecture is capable of supporting plug-and-play systems with a high level of flexibility, scalability, and ease of maintenance. The proposed evaluation framework provides a reproducible quantitative approach to assessing the architectural modularity of renewable power stations, which has been rarely formally discussed in the literature.